Desenvolvimento de estratégias de alimentação para produção de ramnolipídios por Pseudomonas aeruginosa LBI 2A1 em biorreator - Silva, Vinícius Luiz da [UNESP] (2014)
Surfactants are amphipathic molecules that due to the presence of regions with different polarities have unique properties such as the ability to reduce the interfacial and surface tension. The biosurfactants are biological molecules that can be synthesized by a wide range of organisms, however the most studied producers are microorganisms. Despite the numerous benefits of biological surfactants, such as low toxicity, biodegradability and high stability, these compounds are not widely used because of the high production cost. For this reason, this study aims to optimize the production of rhamnolipids in bioreactors, for such was employed cultivation in batch and feed batch. The cultive that achieved the highest production and yield was a batch using 250 g/L of soybean oil as carbon source, the culture reached 36.4 g/L of rhamnolipids and 0.23 g/Lh of productivity. Beyond to increase this bioproduct production, it is important to find new applications for this biossurfactant, helping to aggregate value for them, the present study evaluated two applications for rhamnolipid. The first one evaluated the influence of rhamnolipids on seeds germination. When in contact with surfactants the lettuce seeds had their germination increased 175%, however the seedlings showed a less development, the corn seeds had their germination and seedling favored at 0,025 to 0,05 % w/v concentrations. Regarding soybean seeds there was no effect on germination but favored seedling development. In relation to sunflower seeds, both ,the development and germination, were positively influenced at all concentrations evaluated. The second application evaluated was the rhamnolipids insecticidal potential, against adults and larvae of Aedes aegypti. When used at concentrations 1000 900 800mg/L rhamnolipids eliminated all the larvae of this mosquito species in only 18h, the concentration of 1000mg / L was able to remove 100% of adults and also showed repellency against...